Estudio de los mecanismos de señalización asociados al receptor Mas - Burghi, Valeria (2018)
The Mas receptor (MasR) is a class A Orphan G-protein-coupled receptor (GPCR). Although angiotensin-(1-7) [Ang-(1-7)] has been reported as its putative ligand, the intracellular signaling pathways activated by the MasR remain only partially characterized. In this study we examined MasR-dependent activation of G protein-mediated and ERK mediated signaling pathways. Transfection of HEK293T cells with a wild-type MasR (wt-MasR) construct resulted in a decrease in basal cAMP levels that depended on the amount of wt-MasR protein expressed and was also observed when increasing amounts of mutant MasR lacking the PDZ binding motif were expressed. Pretreatment of wt-MasR expressing cells with pertussis toxin restored basal cAMP levels. Also, cAMP production after forskolin stimulation was lower in cells expressing wt-MasR than in control cells. These results indicate a high level of constitutive receptor activity towards cAMP modulation involving G?i-protein. Treatment with Ang(1-7) increased p-ERK levels in both wt-MasR and in mock-transfected HEK293T cells. MasR-overexpression lowered this effect. In view of these results we analized endogenous receptors expression different from MasR that could be mediating Ang-(1-7) effect. As MasR has been suggested to participate in cardiovascular and renal functions, comprehensive pharmacological characterization of MasR signaling is essential for developing clinical therapeutics targeting MasR function.